The effect of the Duit model on the critical thinking skills of primary school students in mathematics (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of the Duit model on the critical thinking skills of primary school students in mathematics. To achieve the research goal, the researcher followed the experimental method and developed the null hypothesis, which states (there is no statistically significant difference at the significance level (0.05) between the average scores of the experimental group students who will study mathematics according to the (Duit) model and the average scores of the control group students who will study the same subject according to the (traditional method) in testing critical thinking skills. The research sample included (60) A student from the fifth primary school in (Al-Duaa School for Boys) affiliated with the General Directorate of Education of Baghdad/Al-Rusafa Second for the academic year (2022-2023), where the experimental group was taught using the (Duit) model and their number was (30) students, while the control group was taught using the method The number of students in the regular school was (30), where the two research groups were rewarded with the variables (chronological age in months, intelligence test, previous knowledge, and previous achievement in mathematics), and the research tool was prepared, which is a critical thinking skills test consisting of (25) items from Multiple choice type with four alternatives, and the results concluded that there is a statistically significant difference at the level (0.05) in the critical thinking of students in the two research groups (experimental and control), and thus the null hypothesis is rejected and the alternative hypothesis is accepted, and the researcher left With several recommendations and proposals, the most important of which is the inclusion in mathematics curricula of constructivist education models, including the (Duit) model because of its importance in expanding students’ understandings and motivating them to learn, and it was suggested to use the (Duit) model with other variables such as achievement and logical and mathematical thinking.. .etc